Highly active and controllable MOF-derived carbon nanosheets supported iron catalysts for Fischer-Tropsch synthesis. (March 2021) - Zhao, Qiao; Huang, Shouying; Han, Xiaoxue; Chen, Jiajia; Wang, Junhu; Rykov, Alexandre; Wang, Yue; Wang, Meiyan; Lv, Jing; Ma, Xinbin
Abstract: N-doped carbon materials as catalyst supports have shown great superiority because of rich porosity, tunable metal-support interaction and electronic promotion effect. Controllable fabrication of carbon materials with specific morphology and different configurations provides wider possibilities for applications in catalysis. Herein, N-doped carbon nanosheets (CNS) were successfully synthesized by using monoclinic ZIF-8 nanosheets as templates. Compared with commercial active carbon and cubic ZIF-8 particles-derived carbon particles, the derived CNS exhibit superior graphitization degree and electronic effect. Consequently, the promoted Fe carburization improved the intrinsic activity for Fe/CNS catalysts in FTS. Further investigation on pyrolysis temperature achieved tunable configuration and content of N dopant. XPS, Raman, Mössbauer spectroscopy, TEM, H2 -TPR etc. were combined to elucidate the promotion effect of CNS on dispersion, electronic properties and formation of Fe carbides. By correlating the composition and structure to catalytic performance in FTS, we illustrated the significance of carbon materials in Fe supported catalysts. Graphical abstract: Image 1 Highlights: Controllable synthesis of N-doped carbon nanosheets was achieved by pyrolyzing MOF strategy. Fe supported on MOF-derived carbon nanosheets showed great performance in F-T synthesis. Appropriate graphitization degree and more pyrrolic N are beneficial to CO conversion. The promotion effect on F-T synthesis is due to the modified electronic structure and transfer.